Hyperbaric Oxygen Therapy (HBOT) untuk Pasien Tuli Mendadak - Laporan Kasus - Agustinawati, Kadek Rina; Purwaningsih, Luh Putu Dhena; Wirasatya, Komang Krisna Nugraha (PT Kalbe Farma Tbk., 2026)
Introduction: Sudden deafness or sudden sensorineural hearing loss (SSNHL) is defined as sensorineural hearing loss of more than 30 dB at three consecutive frequencies occurring within 3 days. The condition is usually unilateral and often idiopathic. The etiology is still not known. Early diagnosis and prompt treatment are essential to improve hearing recovery. Case: A 62-year-old Balinese male presented with sudden decreased hearing for approximately one week accompanied by tinnitus. The patient denied previous history of cough, cold, vomiting, allergies, sinusitis, autoimmune disease, anemia, or other systemic diseases. There was no history of trauma or rhinoplasty. Pure tone audiometry showed severe mixed hearing loss in the right ear and moderate sensorineural hearing loss in the left ear. The patient received combination therapy consisting of methylprednisolone, mecobalamin, and hyperbaric oxygen therapy (HBOT). Discussion: HBOT increases oxygen delivery to the inner ear and may enhance cochlear metabolism and microcirculation. Several studies have reported improved outcomes when HBOT therapy is combined with corticosteroid therapy. Conclusion: This case demonstrats that HBOT therapy combined with corticosteroids may provide significant hearing improvement in patients with sudden deafness.